Alkaline organosolv pretreatment of corn stover for enhancing the enzymatic digestibility. (October 2018) - Yuan, Wei; Gong, Zhiwei; Wang, Guanghui; Zhou, Wenting; Liu, Yi; Wang, Xuemin; Zhao, Mi
Graphical abstract: Highlights: A sodium hydroxide-methanol solution (SMs) pretreatment was firstly described. This pretreatment offers advantages in enzyme accessibility and energy consumption. 97.5% glucan and 83.5% xylan were preserved in the regenerated corn stover. The enzymatic digestibilities of glucan and xylan were 97.2% and 80.3%, respectively. The enzyme susceptibility was explained by their physicochemical characteristics. Abstract: In the present study, a sodium hydroxide-methanol solution (SMs) pretreatment of corn stover was described to overcome biomass recalcitrance for the first time. Effects of sodium hydroxide loading, solid-to-liquid ratio, processing time and temperature on enzymatic saccharification were studied in detail. The SMs pretreatment could significantly enhance the enzyme accessibility of corn stover, minimize the degradation of sugar polymers, and decrease the energy consumption. 97.5% glucan and 83.5% xylan were preserved in the regenerated corn stover under the optimal condition. Subsequent enzymatic digestibilities of glucan and xylan reached 97.2% and 80.3%, respectively. The enzyme susceptibility of the regenerated samples was explained by their physical and chemical characteristics. This strategy provides a promising alternative for better techno-economic of the lignocelluloses-to-sugars routes.